Asian Monsoon variation over the late Neogene–early Quaternary recorded by Anisotropy of Magnetic Susceptibility (AMS) from Chinese loess. (18th April 2016) - Xie, Xingjun; Xian, Feng; Wu, Zhenkun; Kong, Xianghui; Chang, Qiufang
Abstract: This paper discusses the Anisotropy of Magnetic Susceptibility (AMS) records during late Neogene to early Quaternary from the Lantian loess section near the southern margin of the Chinese Loess Plateau. The AMS results for this site are shown to reflect variations in the direction of the paleomonsoon. The Lantian loess sediments are largely aeolian in origin, but also include a thin layer that exhibits secondary aqueous depositional features. The major ellipsoid axis AMS orientations in the loess samples indicate a pervasive Northwest–Southeast directional component since the late Neogene. Since that time, the W–E component gradually overtakes the N–S component, which may explain the trend toward increased aridity during that time. Finally, a local heavy rainfall event seemingly occurred in the Lantian region about 2.6 Ma, which may have been responsible for the aqueous redeposition of sediments observed in L33 layer in this study.